Quercetin Antagonizes Glucose Fluctuation Induced Renal Injury by Inhibiting Aerobic Glycolysis via HIF-1α/miR-210/ISCU/FeS Pathway - Xu, Wei-long; Liu, Su; Li, Nan; Ye, Li-fang; Zha, Min; Li, Chang-yin; Zhao, Yue; Pu, Qiang; Bao, Jin-jing; Chen, Xing-jie; Yu, Jiang-yi; Pei, Ying-hao (Frontiers in Medicine, 2021)
Background and Objective: Glucose fluctuation (GF) has been reported to induce renal injury and diabetic nephropathy (DN). However, the mechanism still remains ambiguous. Mitochondrial energy metabolism, especially aerobic glycolysis, has been a hotspot of DN research for decades. The activation of HIF-1α/miR210/ISCU/FeS axis has provided a new explanation for aerobic glycolysis. Our previous studies indicated quercetin as a potential therapeutic drug for DN. This study aims to evaluate levels of aerobic glycolysis and repressive effect of quercetin via HIF-1α/miR210/ISCU/FeS axis in a cell model of GF. Methods: The mouse glomerular mesangial cells (MCs) were exposed in high or oscillating glucose with or without quercetin treatment. Cell viability was measured by CCK8 assay. Aerobic glycolysis flux was evaluated by lactate acid, pH activity of PFK. Apoptosis level was confirmed by Annexin V-APC/7-AAD double staining and activity of caspase-3. TNF-α and IL-1β were used to evaluate inflammation levels. Results: GF deteriorated inflammation damage and apoptosis injury in MCs, while quercetin could alleviate this GF-triggered cytotoxicity. GF intensified aerobic glycolysis in MCs and quercetin could inhibit this intensification in a dose-dependent manner. Quercetin prevented activities of two FeS-dependent metabolic enzymes, aconitase and complex I, under GF injury in MCs. The mRNA expression and protein contents of HIF-1α were increased after GF exposure, and these could be alleviated by quercetin treatment. Knockdown of ISCU by siRNA and Up-regulating of miR-210 by mimic could weaken the effects of quercetin that maintained protein levels of ISCU1/2, improved cell viability, relieved inflammation injury, decreased apoptosis and reduced aerobic glycolysis switch in MCs. Conclusion: Quercetin antagonizes GF-induced renal injury by suppressing aerobic glycolysis via HIF-1α/miR-210/ISCU/FeS pathway in MCs cell model. Our findings contribute to a new insight into understanding the mechanism of GF-induced renal injury and protective effects of quercetin.